Wise blindness: reinterpreting false information engagement through a thematic analysis - Wuyao Ding; Yan Ge (Social Influence)
This study challenges ‘gullibility’ as the primary driver of false information engagement. Thematic analysis of 30 interviews in China reveals two themes. Firstly, multifaceted motivations underlying strategic engagement: Individuals intentionally interact with false information for goal attainment, emotional appeasement, rational trade-offs, or pragmatic acceptance of low-stakes content. Secondly, contextual gaps in cognitive adaptation: Susceptibility arises from overthinking under pressure, exploitation of routine behaviors, and technological challenges. Findings reframe ‘gullibility’ as socially constructed through individual-context interactions, advocating for context-sensitive analyses of false information engagement.